2010
DOI: 10.1007/s00296-010-1610-3
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of soluble CD21 in patients with systemic sclerosis

Abstract: Systemic sclerosis (SSc) is a systemic disorder that typically results in fibrosis of the skin and multiple internal organ systems. Although the precise mechanism is unknown, overproduction of extracellular matrix proteins, including collagens and fibronectins, and aberrant immune activation might be involved in the pathogenesis. The soluble cluster of differentiation 21 (sCD21) represents the extracellular portion of the CD21 glycoprotein that is released by shedding from the cell surfaces into plasma. sCD21 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…For instance, the level of CD21 in serum of patients with lupus, rheumatoid arthritis, Sjogren’s syndrome, and systemic sclerosis is decreased [19,23,24]. In addition, there is some evidence regarding the role of CD21 in the pathogenesis of MS. For instance, CD21 serves as a receptor for Epstein-Barr virus, which per se is suggested to be related to the MS [25,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the level of CD21 in serum of patients with lupus, rheumatoid arthritis, Sjogren’s syndrome, and systemic sclerosis is decreased [19,23,24]. In addition, there is some evidence regarding the role of CD21 in the pathogenesis of MS. For instance, CD21 serves as a receptor for Epstein-Barr virus, which per se is suggested to be related to the MS [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it may be plausible to suggest CD8 + T cells as chief cells that associate CD21 with MS disease. Considering the influence of age and interferon-β therapy on CD21 [23,27,28], one possible strength of the current study is that we controlled the effects of these two potentially confounding variables.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that the level of sCR2 was elevated in the cerebrospinal fluid of multiple sclerosis patients and correlated with the severity of the disease. Furthermore, an in vitro study showed that sCR2 inhibited the cleavage of C3 into iC3b, which mediated the clearance of debris from the inflammatory site [151-153]. These findings suggest a novel function of sCR2 in human neuro-inflammation.…”
Section: Complement In Ischemic Strokementioning
confidence: 99%
“…Levels of sCD21 were found lower in SSc than in HC, especially in case of lcSSc and ILD, but not associated with autoantibody profile (46). Concentrations of sCD23 in SSc were higher than in HC in a single study (47).…”
Section: Soluble Markers Of B Cell Activation In Systemic Sclerosismentioning
confidence: 70%